Design and Preparation of Wave-Transmitting Reinforcing Coatings for Multifunctional Ceramic Composite Antenna Windows. (November 2019) - Sun, Chenggong; Zhang, Qingli; Zhang, Xunhu; Xing, Zhengpeng; Wang, Yanyan; Cheng, Honghao; Jiang, Liping
Abstract: For obtaining multifunctional ceramic composite antenna windows with integrated function including low density, wave-transmission and thermal insulation, the design and preparation of reinforcing coatings on ceramic matrix was discussed in detail in this work. With quartz glass chopped fiber as the major constituent for matrix, borosilicate glass was selected as the main phase for reinforcing coatings, and functional filler was added to match the coefficient of thermal expansion between the two components. According to the performance testing of the as-prepared samples, content of B2 O3 in SiO2 /B2 O3 binary system and sintering temperature showed a marked impact on the microstructure, density and thermal behaviour of the ceramics. Densified coatings were prepared at 1160°C after sintering for 1h with 20% B2 O3 in borosilicate glass, which bond well with the substrate and have radiation coefficient of 0.85 and linear expansion coefficient of (1.77∼2.39)×10-6/°C (200∼1000°C). Stronger matrix, better ablation resistance and dielectric properties are expected to be integrated in the obtained sample pieces, which can be a good candidate as effective thermal insulation materials for aerospace aircrafts at high flight Ma.